Drugs and Drug Candidates: Year in Review - Jean Jacques Vanden Eynde (MDPI AG, 2024)
First of all, I would like to wish you, readers, authors, referees, Editorial Board Members, and colleagues of the editorial offices, a Happy New Year filled with plenty of familial joys and professional achievements [...]